Design and THD Analysis of 5-Level Cascaded Multilevel Inverter - Hamdan, Muhammad Faiz Rashkin; Wahyu Mulyo Utomo (Evolution in Electrical and Electronic Engineering, 2023)
One of the electronic equipment that gives researchers concern for the enhancement of generating a neat power source is an inverter, which can be defined as a device or electric circuit that converts direct current (DC) to alternating current (AC). As part of this project, a model of a multilevel inverter that uses a 5-level cascaded H-bridge of a multilevel DC-AC inverter is going to be developed which will reduce the total harmonic distortion (THD). In this experiment, the total harmonic value of a traditional 3-level multilevel inverter is compared with the outcome of a 5-level multilevel inverter. In particular, the utilisation of a cascaded H-Bridge architecture in conjunction with a sinusoidal pulse width modulation (SPWM) result in greater output power with a multilevel configuration. The experimental result that has been included demonstrates how effective the inverter that has been proposed is. As a result, the goal of this project is to analyse and get a lower amount of THD. This project has obtained the voltage output waveform of a 5-level inverter hardware circuit and its THD% which will be covered in output parts.